Application of the RAND‐UCLA Appropriateness Methodology to a Large Multidisciplinary Stakeholder Group Evaluating the Validity and Feasibility of Patient‐Centered Standards in Geriatric Surgery. (22nd March 2018) - Berian, Julia R.; Baker, Tracey L.; Rosenthal, Ronnie A.; Coleman, JoAnn; Finlayson, Emily; Katlic, Mark R.; Lagoo‐Deenadayalan, Sandhya A.; Tang, Victoria L.; Robinson, Thomas N.; Ko, Clifford Y.; Russell, Marcia M.
Abstract : Objectives: To explore (1) differences in validity and feasibility ratings for geriatric surgical standards across a diverse stakeholder group (surgeons vs. nonsurgeons, health care providers vs. nonproviders, including patient‐family, advocacy, and regulatory agencies); (2) whether three multidisciplinary discussion subgroups would reach similar conclusions. Data Source/Study Setting: Primary data (ratings) were reported from 58 stakeholder organizations. Study Design: An adaptation of the RAND‐UCLA Appropriateness Methodology (RAM) process was conducted in May 2016. Data Collection/Extraction Methods: Stakeholders self‐administered ratings on paper, returned via mail (Round 1) and in‐person (Round 2). Principal Findings: In Round 1, surgeons rated standards more critically (91.2 percent valid; 64.9 percent feasible) than nonsurgeons (100 percent valid; 87.0 percent feasible) but increased ratings in Round 2 (98.7 percent valid; 90.6 percent feasible), aligning with nonsurgeons (99.7 percent valid; 96.1 percent feasible). Three parallel subgroups rated validity at 96.8 percent (group 1), 100 percent (group 2), and 97.4 percent (group 3). Feasibility ratings were 76.9 percent (group 1), 96.1 percent (group 2), and 92.2 percent (group 3). Conclusions: There are differences in validity and feasibility ratings by health professions, with surgeons rating standards more critically than nonsurgeons. However, three separate discussion subgroups rated a high proportion (96–100 percent) of standards as valid, indicating the RAM can be successfully applied to a large stakeholder group.